Shariah Market Based On Social Media; A Strategic Conflict For Improving Sale - Eka Anggraini Aritonang; Sri Mauliza (Proceeding International Seminar of Islamic Studies, 2019)
: The emergence of instantaneous products has a major impact on people's perspectives and behavior. Many people do not want to be difficult in owning a house, so many companies use this great opportunity to build a medium business engaged in developers. The business undertaken began with the use of own capital, which has now expanded to larger businesses aimed at supporting the government's "One Million Houses" program. The sharia marketing strategy that is applied prioritizing the sharia element brings a lot of blessing, this has a major impact on increasing consumer response and blessing profit profits. Initially using a promotional strategy through print media was considered less effective. And now increasingly expanding its wings by using a Facebook account as a means of accurate promotion right to make it easier to convey business product information to the wider community. In this case the researchers used the research method "Qualitative Descriptive Analysis" with the technique of collecting data "observation, and documentation".